KARAKTERISTIK SINGKAPAN BATUAN BEKU DAERAH CISAMPIH, DESA CITATAH, KECAMATAN CIPATAT, SEBAGAI LOKASI PRAKTIK KERJA LAPANGAN PELATIHAN BIDANG GEOLOGI - Pudjo Asmoro; Aminul Wahib; Iwan Fahlevi Setiawan (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2018)
Igneus rocks in the area Cisampih are only a small hillocks that covering about 1.5 hectares in the Citatah hills which is famous for limestones mining and marble. This mining also penetrated to some small hills of igneous rock,so its appearance as a dike through nearby rocks becomes clearer, as well as its burning effects. The altered part of limestone into marble in this area is interpreted as a result of this intrusion. The research was conducted by using geological mapping method, to know the lateral or vertical spread of existing rock outcrops, and to know the connection between the rocks. Petrographic analysis was conducted to determine the mineralogy composition of the rock, its function to name the rock type in more detail. The result of the research shows that the research area is composed by claystone which is crushed by limestone and the claystone are extruded by igneous rock but it doesn’t break through the limestone. This situation makes the area to be more attractive at least for field work practice trainees, geology students excursion, because it is supported by its relatively easy accessibility and close to Bandung city.